Gallic acid: A promising bioactive agent for food preservation and sustainable packaging development - Istiqomah Rahmawati; Agus Wedi Pratama; Silvia Abdi Pratama; Muhamad Nur Khozin; Afrinal Firmanda; Fery Haidir Irawan; Asranudin; Arif Nur Muhammad Ansori; Teguh Hari Sucipto (Case Studies in Chemical and Environmental Engineering)
The growing global population challenges the food industry to ensure it remains safe for consumption. Food waste caused by imbalances between production and handling creates significant economic, environmental, and social risks. However, packaging technology innovation has emerged as a powerful tool, offering a solution by extending shelf life and maintaining food product quality. Consumers' increasing interest in eco-friendly packaging has driven research into renewable materials and low-toxicity bioactive components. Gallic acid, a promising phenolic compound, holds potential for food preservation and sustainable packaging development. Its antibacterial and antifungal properties against resistant microbes and biofilm formation, its ability to prevent lipid and protein oxidation, and its potential as a color indicator for monitoring food freshness all contribute to food preservation. Its incorporation into edible polymers offers a strategy for innovative edible packaging. Depending on the dosage and material composition, loading gallic acid within the polymer matrix can improve packaging properties, including UV barrier, mechanical strength, and water vapor and oxygen permeability. This article reviews the potential of gallic acid for developing biodegradable, active, intelligent, and edible packaging. Future directions include evaluating gallic acid's toxicity, dispersion within the matrix, pro-oxidative activity, compatibility with biodegradable polymers (especially those derived from agricultural by-products), migration into food products, and stability under different environmental conditions. The sustainability perspective (environment, economic, and social) is also discussed.